Effectiveness of tobacco control television advertising in changing tobacco use in England: a population‐based cross‐sectional study. (10th March 2014) - Sims, Michelle; Salway, Ruth; Langley, Tessa; Lewis, Sarah; McNeill, Ann; Szatkowski, Lisa; Gilmore, Anna B.
Abstract Aim To examine whether government‐funded tobacco control television advertising shown in England between 2002 and 2010 reduced adult smoking prevalence and cigarette consumption. Design Analysis of monthly cross‐sectional surveys using generalised additive models. Setting England. Participants More than 80 000 adults aged 18 years or over living in England and interviewed in the Opinions and Lifestyle Survey. Measurements Current smoking status, smokers' daily cigarette consumption, tobacco control gross rating points (GRPs—a measure of per capita advertising exposure combining reach and frequency), cigarette costliness, tobacco control activity, socio‐demographic variables. Findings After adjusting for other tobacco control policies, cigarette costliness and individual characteristics, we found that a 400‐point increase in tobacco control GRPs per month, equivalent to all adults in the population seeing four advertisements per month (although actual individual‐level exposure varies according to TV exposure), was associated with 3% lower odds of smoking 2 months later [odds ratio (OR) = 0.97, 95% confidence interval (CI) = 0.95, 0.999] and accounted for 13.5% of the decline in smoking prevalence seen over this period. In smokers, a 400‐point increase in GRPs was associated with a 1.80% (95%CI = 0.47, 3.11) reduction in average cigarette consumption in the following month and accounted for 11.2% of the total decline in consumption over the period 2002–09. Conclusion Government‐funded tobacco control television advertising shown in England between 2002 and 2010 was associated with reductions in smoking prevalence and smokers' cigarette consumption.